India : 2007 Article IV Consultation; Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for India. (IMF Staff Country Reports; Country Report, 2008)
India's strong growth and macroeconomic stability is owed to its sound macroeconomic policies and past structural reforms. Swelling capital inflows have highlighted the key policy challenges: managing financial globalization and tackling the supply constraints to growth. Monetary operations and communications are adapting to financial globalization. The Reserve Bank of India maintains a strong focus on preserving financial stability. Further fiscal consolidation is essential to sustain inclusive growth and the financial globalization. Structural reforms to make the economy more flexible are key to competitiveness and inclusive growth.